ENHANCING STUDENTS’ CONTENT AND ORGANIZATION OF WRITTEN TEXTS THROUGH COOPERATIVE LEARNING ACTIVITIES (English Education Journal, 2013)
Siswa seringkali mengalami kesulitan dalam membuat karangan, khususnyadalam pengembangan isi dan sistematika penyusunan karangan. Penelitian iniberusaha memecahkan isu tersebut dengan melibatkan siswa di dalam berbagaikegiatan pembelajaran kooperatif. Dua siklus penelitian tindakan kelas telahdiimplementasikan di ke kelas XI. Dua tipe text yang diajarkan kepada 26 siswayakni report dan narrative. Data diperoleh dari jurnal harian guru, karangansebelum siklus, dan karangan setelah siklus. Data kedua diperoleh dari kumpulankarya anak. Dengan menjelaskan data kualitatif dan kuantitatif, penelitian inimenjelaskan proses perubahan yang berkaitan dengan karangan. Dalam duasiklus tersebut kemampuan menulis siswa meningkat. Peningkatan di bidang isiditunjukan dengan peningkatan nilai dari taraf buruk ke taraf memuaskan. Isitulisan siswa yang awalnya tidak tersusun dengan baik dan dengan ide terputusdapat berubah menjadi tulisan dengan ide yang jelas dilengkapi dengan informasiyang memadai. Peningkatan di bidang organisasi karangan meningkat dari burukke sangat baik. Awalnya karangan siswa tidak sistematis namun mereka berhasilmeningkat ke karangan yang terstruktur dengan idea yang mengalir secara logismengikuti pola karangan yang dianut. Peningkatan di bidang isi adalah 3.43sedangkan peningkatan dalam organisasi karangan adalah 3.46.Students often have problems in writing, especially in developing contents and organizingideas to write. The present study attempted to improve my students’ contents and organizationthrough engaging them in cooperative learning activities. Two cycles of an action researchwere implemented to the eleventh grade students. Two types of genre were taught: report andnarrative. There were 26 students involved. The primary data were the teacher’s daily journal,the students’ pre-cycle writing, and the students’ post-test writing. The secondary data werethe students’ artifacts. After two cycles of action research, the students gained improvement intheir writing contents and organization. In the area of contents, the students improved fromthe level of fair to poor to excellent to very good. They were able to move from scratch andchoppy writing to the level of writing with ideas clearly stated completed with knowledgeableinformation. In the area of organization, they were able to move from the level of fair to poorin which they were lacking of logical sequencing to the excellent level in which the were ableto organize ideas in a logical order. The improvement in the area of content was 3.43 and theimprovement in the area of text organization was 3.46.